2003
DOI: 10.1097/00008390-200308000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Ocular melanoma is not associated with CDKN2A or MC1R variants — a population-based study

Abstract: Germline variants in the melanocortin 1 receptor gene (MC1R) and the p16 gene (CDKN2A) are associated with an increased risk of cutaneous melanoma. The frequency of these germline variants was examined in a populationbased, incident series of 62 ocular melanoma cases and ethnicity-matched population controls. In both cases and controls, 59% of individuals carried at least one MC1R variant and there were no significant differences in the frequency of any of the five most common variants of MC1R. We also found n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This suggests that certain MC1R variants can exert an effect on melanoma tumorigenesis in a dual manner, both as a determinant of fair skin and as a component in an independent additional pathway (Palmer et al, 2000;Van der Velden et al, 2001). Our data support the findings of Metzelaar-Blok et al (2001) and the recent study reported by Vajdic et al (2003), who found no relationship between variation in MC1R and risk of uveal melanoma. Moreover, pooling data from all three studies provide no evidence that variants confer an increased risk of uveal melanoma.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This suggests that certain MC1R variants can exert an effect on melanoma tumorigenesis in a dual manner, both as a determinant of fair skin and as a component in an independent additional pathway (Palmer et al, 2000;Van der Velden et al, 2001). Our data support the findings of Metzelaar-Blok et al (2001) and the recent study reported by Vajdic et al (2003), who found no relationship between variation in MC1R and risk of uveal melanoma. Moreover, pooling data from all three studies provide no evidence that variants confer an increased risk of uveal melanoma.…”
Section: Discussionsupporting
confidence: 93%
“…Two research groups have previously reported on the relationship between MC1R variants and risk of uveal melanomaMetzelaar-Blok et al (2001) based on analysis of 162 patients and Vajdic et al (2003) based on analysis of 62 patients. In both studies, there was no difference in the frequency of variants in cases compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…There is no statistically significant association of the MC1R variants with ocular melanoma in both studies. 41,42 This could be the consequence of strata with small numbers of cases and controls with the respective genotypes in both analyses, and it does not necessarily rule out a possible association between MC1R variants and uveal melanoma risk.…”
Section: Discussionmentioning
confidence: 99%
“…The methods varied slightly between the centers, and examples of methods can been found in Vajdic et al (32) and Kanetsky et al (33). We checked that the distribution of MC1R variants were in Hardy–Weinberg equilibrium; no departure from Hardy–Weinberg equilibrium at the 5% significance level was found.…”
Section: Methodsmentioning
confidence: 99%